A legal geography of the regulation of contaminated land in Williamtown, New South Wales. (27th October 2020) - Legg, Rupert
Abstract: Legal geographers have recently been interested in interlegality: the interactions between different legal orders governing one particular space. Contaminated land is one such space governed by multiple legal orders; however, it is yet to receive great attention in legal geography. In Australia, different authorities and bodies cooperate together in a responsive regulatory framework to prevent contamination and then manage cases where contamination has occurred, although this process is mostly coordinated at the level of the state. This article evaluates the framework by reference to a case where the contamination, by perfluoroalkyl and polyfluoroalkyl substances (PFAS), has crossed jurisdictional boundaries in Williamtown, in New South Wales, Australia. This cross‐boundary incursion has complicated management responses, and may have resulted in contradicting forms of regulatory implementation by different legal orders and a break down in accountability. Ultimately, such findings point to the need for the current regulatory framework to be adapted to better deal with situations of spatial and legal complexity.